Key topics in pulmonary vascular diseases (assembly 13) from the European Respiratory Society 2018 Parisian Congress - Ramjug, Sheila; Noordegraaf, Anton Vonk; Delcroix, Marion (Journal of Thoracic Disease, 2018)
Pulmonary vascular disease was a key topic at this years’ European Respiratory Society Annual Congress and the first year of the creation of assembly 13. We therefore aim to concentrate on three key hot topics from the Congress and its impact on pulmonary vascular disease in clinical practice.